Capacity Enhancement of Productivity and Product Marketing Through Construction Project Management of Interior Spaces - Pratiwi Juniar Achmad Gani; Ackhriansyah Ahmad Gani; Andi Muhammad Ikhsan (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The execution of interior construction work involves a complex series of processes carried out in parallel and interdependent. Additionally, the nature of the work is highly specialized, with tasks being divided according to the characteristics and professions of those performing them. It is crucial to maintain regular coordination and control to ensure that all activities are consistent and aligned throughout building construction. This, of course, requires the involvement of a team capable of managing the project, creating work plans, and coordinating with other teams. They need strong communication skills, problem-solving abilities, and effective leadership. The success of an interior construction project can be measured by the production of high-quality work, adherence to the planned budget, and timely completion in accordance with agreements. Therefore, performance-oriented control is necessary to complete an interior construction project successfully. In the management of interior construction projects, the concept of earned value integrates cost and time. By applying this concept, the overall performance of an interior construction project, as well as that of individual work packages, can be identified and predicted. The results of this performance evaluation can serve as an early warning if inefficiencies arise during the completion of the interior construction project. This community service activity, aimed at empowering interior construction workers, embodies the effort to develop project management capabilities within this field. This activity aims to provide a project management guide for interior construction that supports the development of team capabilities. The method of this community service activity was carried out through socialization and community empowerment activities related to the stages of an interior construction project management process to improve work productivity. With controlled work planning, productivity improvement could also be achieved through enhanced job promotion. The results of this activity showed that the implementation of the service activity was deemed successful, with a significant improvement in test scores, from a very low knowledge level of 0-40 to a very good knowledge level of 86-100. In the execution of interior construction, the ability to organize and manage work was required to achieve the best results and market them directly according to the chosen strategy. Additionally, partner feedback indicated that they strongly agreed with the implementation of this program.